RESPON PEMBERIAN PUPUK NPK MUTIARATERHADAP PERTUMBUHAN DAN HASIL 3 VARIETAS JAGUNG MANIS - Fitrianty, Fitrianty; Tjokrodiningrat, Suryati; Soenarsih, Sri; Sudjud, Suratman; Samad, Sofyan; Hadun, Ramli (Universitas Khairun, 2025)
This research aims to analyze the effect of increasing the dose of NPK Mutiara 16-16-16 fertilizer on 3 varieties of sweet corn (Zea Mays Saccharata Sturt). This research was carried out in Tuokona Village, South Bacan District in August-December 2024. The research used a Factorial Randomized Block Design with 2 treatment factors, namely the first factor was plant variety consisting of the Paragon variety (J1), the Bonanza variety (J2) and the Super sweet variety (J3). The second factor consists of fertilizer doses P1 (5 gr), J2 (10 gr) and J3 (15 gr). The research data were analyzed using analysis of variance (ANOVA) and continued with the Duncan test (DMRT) 5% for data that was significantly different. Research results Plant varieties had significantly different effects on observations of leaf area, flower age, fruit length, fruit diameter and the best treatment was found in the Bonanza variety and the Paragon variety. The treatment dose of NPK Mutiara 16-16-16 fertilizer resulted in the best treatment at P3 (15 g/plant) for plant height.